Placebo Models - Molnár Imre (STRATEGIC MANAGEMENT: INTERNATIONAL JOURNAL OF STRATEGIC MANAGEMENT AND DECISION SUPPORT SYSTEM IN STRATEGIC MANAGEMENT, 2013)
Based on international research conducted in 2002, only one- third of the 288 researched companies used any kind of methodology when implemented changes. According to a non- representative survey carried out in Hungary in 2011 in the topic of change management, only 10 % of all the companies taking part in the survey applied change management models found in the professional literature. Nevertheless, almost half of them were still satisfied with the outcome. From the point of view of the success of the changes, choosing the methodology is not a guarantee by itself. We can especially not predict what the situation of the company will be at the end of the procedure in compar- ison with the initial status since, in the meantime, the change itself is taking place, too.